Pengaruh Latihan Multiple To Box Jump Terhadap Kemampuan Blocking Dalam Permainan Bola Voli Ekstrakulikuler Di Mtsn 02 Kabupaten Kepahiang - Nanda Saputra; Dody Ertanto; Asnawati Asnawati (Journal Of Dehasen Educational Review, 2026)
This study aims to determine the effect of multiple to box jump training on blocking skills in volleyball extracurricular students at MTSN 02 Kepahiang Regency. Using the total sampling method to determine the number of respondents, 16 volleyball extracurricular students at MTSN 02 Kepahiang Regency were obtained. This experimental study used a One Group Pre-test – Post-test design, which is a pre-experimental design that includes a pre-test (test before treatment) and a post-test (test after treatment) in one group. Data collection was carried out using test scores. Descriptive data analysis and t-tests were used. The results of this study indicate that multiple to box jump training has an effect on the blocking ability of volleyball extracurricular students at MTSN 02 Kepahiang Regency, with a t-value of 3.451 and a t-table value of 1.753 at a significance level of α = 0.05 and df = 16.